Novel aspects of Cell Division Cycle and Apoptosis Regulator 1 (CCAR1) protein in Morus notabilis: an in silico approach. (2nd October 2020) - Mondal, Raju; Das, Poushali
ABSTRACT: Cell division cycle and apoptosis regulator 1 (CCAR1) is a deleted in breast cancer domain containing protein and their molecular roles in the animal system are well characterized. So far study on CCAR1 protein has not available in the plant system. The domain-based phylogenetic study clearly indicates that the CCAR1 protein has widely distributed throughout the plant kingdom. Intron-less CCAR1 gene encoded protein comprises five conserved domain and huge intrinsic disorder. Functional annotation of cis -regulatory elements (CREs) reveales that a wide range of potential transcription factor binding sites (TFBSs) are present in CCAR1 gene promoter. Besides that potential miRNA targets those control post-transcriptional regulations are also identified in the present study. Furthermore, gene ontogeny (GO) analysis revealed that CCAR1 have dynamic role in a wide number of cellular and metabolic processes. In this study, we first report the regulation, functional and structural property of CCAR1 transcript and protein which will help to assist crop improvement by manipulating CCAR1.